An application of clustering for strategic group analysis - Harrigan, Kathryn Rudie (Strategic Management Journal, 1985)
Abstract Taxonomies, factor analysis and clustering are discussed as tools to investigate the structure of competitors within an industry (‘strategic groups’). An example using cluster analysis is presented as one means of operationalizing this concept. Careful definition and selection of the dimensions used to identify the boundaries between strategic groups (their mobility barriers) are particularly crucial in the effective application of analytical tools.